Complex dichotomous links of nonalcoholic fatty liver disease and inflammatory bowel disease: exploring risks, mechanisms, and management modalities - Kanishk Aggarwal; Bhupinder Singh; Abhishek Goel; Durgesh Kumar Agrawal; Sourav Bansal; Sai Gautham Kanagala; Fnu Anamika; Aachal Gupta; Rohit Jain (Intestinal Research)
Nonalcoholic fatty liver disease (NAFLD) has been shown to be linked to inflammatory bowel disease (IBD) due to established risk factors such as obesity, age, and type 2 diabetes in numerous studies. However, alternative research suggests that factors related to IBD, such as disease activity, duration, and drug-induced toxicity, can contribute to NAFLD. Recent research findings suggest IBD relapses are correlated with dysbiosis, mucosal damage, and an increase in cytokines. In contrast, remission periods are characterized by reduced metabolic risk factors. There is a dichotomy evident in the associations between NAFLD and IBD during relapses and remissions. This warrants a nuanced understanding of the diverse influences on disease manifestation and progression. It is possible to provide a holistic approach to care for patients with IBD by emphasizing the interdependence between metabolic and inflammatory disorders.